2021
DOI: 10.3390/ph14060546
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Glycosyl Flavonoids as Anti-Coronaviral Agents

Abstract: The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread all over the world, creating a devastating socio-economic impact. Even though protective vaccines are starting to be administered, an effective antiviral agent for the prevention and treatment of COVID-19 is not available yet. Moreover, since new and deadly CoVs can emerge at any time with the potential of becoming pandemics, the development of therapeutic agents against potentially deadly CoVs is a resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 128 publications
0
20
0
Order By: Relevance
“…Therefore, we propose that glycosylation plays an important inhibitory role in the binding mechanism of flavonoids against these targets ( Table S1 ). Such flavonoids could mechanistically block attachment and disrupt the entry of virions into host cells while interfering with various stages of viral replication, translation, and polyprotein processing in order to prevent the release of the viruses [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we propose that glycosylation plays an important inhibitory role in the binding mechanism of flavonoids against these targets ( Table S1 ). Such flavonoids could mechanistically block attachment and disrupt the entry of virions into host cells while interfering with various stages of viral replication, translation, and polyprotein processing in order to prevent the release of the viruses [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glycosylated flavonoids consist of a base flavan structure and sub-class specific –R groups in addition to a sugar moiety such as arabinose, rhamnose, rutinose, galactose, or glucose; which impacts their respective biological activities [ 43 ]. Moreover, flavonoids without sugar moieties are seen to be largely insoluble in water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study demonstrated that flavonoids are able to inhibit both coronavirus protease enzymes 3C-like-protease (3CLpro) and papain-like cysteine protease (PLpro) which play an essential role in viral replication in host membranes (Russo et al 2020). On the other hand, studies have observed that flavonoids contribute to the reduction of ROS accumulation decelerates the coronavirusactivated apoptotic signalling (Diniz et al 2020;Godinho et al 2021). In silico molecular docking studies have been performed to evaluate and validate the inhibitory effect of flavonoids based on the hydrogen-bonding distance between selected amino acid residues of the catalytic site from 3CLpro and PLpro SARS-CoV-2 proteases and flavonoids (Leal et al 2021).…”
Section: Flavonoidsmentioning
confidence: 99%